Kualitas Pelayanan Puskesmas Lubuk Besar Dengan Pendekatan Importance Performance Analysis (IPA) dan Customer Satisfaction Index (CSI) - Wahyudin, Nanang; Masriyatun, Masriyatun; Yusnita, Maya (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study aims to analyze the level of expectation and level of performance to determine the level of conformity and indicators that are the main priority for improvement and patient satisfaction to improve service quality and satisfy patients at the Lubuk Besar Public Health Center. This study uses a quantitative descriptive approach. Sampling was determined by the purposive sampling technique with a total of 100 respondents. Data collection techniques using questionnaires and interviews. The analysis used is Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results showed that the analysis of the IPA method at the level of conformity of the 5 dimensions of service quality at the Lubuk Besar Public Health Center had a value of 73.74% in the appropriate category only on the responsiveness dimension which was still in the quite especially on the speed and accuracy attributes of doctors treating patients, speed and friendliness of administrative staff, ability to respond and resolve patient complaints. The results of the calculation of the CSI method at the Lubuk Besar Health Center by 70% means that the patient is quite satisfied, but the puskesmas still need to make improvements to the attributes that have low values to improve service quality and satisfy patients. Keywords: service quality, puskesmas, performance, IPA, CSI